Sistem Informasi Pengarsipan Buku Berbasis Web Dengan Bahasa Pemograman PHP & MySQL (Studi Kasus: LKP. Intermedia Training Center) - Ahmad Juang Harahap (Journal of Student Development Informatics Management (JoSDIM), 2021)
Intermedia Training Center Training and Training Institute is a Computer Course that stands in Rantauprapat, North Sumatra. The Book Archiving System at the Intermedia Training Center Course and Training Center still uses manual storage if the officer wants to find a book that is information related to the agency's interests, it can ask the officer. Good Management Factor is one of the important factors in Institution Institutions courses. Especially to get information when needed . The Book Archiving System at the Intermedia Training Center Course and Training Center can be a solution for data processing and can provide more accurate information about book data to the foundation. Furthermore, at the stage of system development with the Prototype model. Analysis of the design includes Contex Diagram, Entity Relationship Diagram, and Data Flow Diagrams. The implementation uses Php and MySQL as database processing. The results of tests that have been done can be concluded that with the existence of Web-Based Book Filing System can provide book data information quickly and accurately and make the search process more efficient.